Neutralization antibodies in combination of MCP-1 are as effective as live-attenuated rabies virus in preventing mice from developing rabies - Fu, Z.; Huang, J.; Li, G.; Zhang, G.; Zhou, M. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies virus (RABV) is a neurotropic virus that causes fatal disease in humans and animals. Currently there is no cure for rabies once clinical signs appear. It has been hypothesized that once the virus enters the central nervous system (CNS), neutralizing antibodies in the periphery cannot cross the blood– brain barrier (BBB) into the CNS. Previous studies have demonstrated that treatment with live-attenuated RABV via the intracerebral route 5 days after infection with wild-type viruses can lead to the clearance not only the attenuated, but also the wild-type virus. Direct administration of liveattenuated RABV stimulated high levels of neutralization antibodies and enhanced the BBB permeability. However, direct intracerebral administration of live-attenuated RABV possesses safety concerns. In the present study, neutralization antibodies were administered in conjunction with a chemokine, MCP-1 (known to enhance the BBB permeability), into mice after infection with wild-type virus. Significantly more protection was found in mice treated with this combination when compared to treatment with neutralization antibodies alone without MCP-1. Furthermore, the combined treatment with neutralization antibodies and MCP-1 is as effective as the live-attenuated RABV in preventing mice from developing rabies. These studies further demonstrate that enhancement of the BBB is critical for immune effectors in the periphery to enter into the CNS to clear RABV.